Secretory Iga Sebagai Bagian Reaksi Sistem Imunitas Mukosa Oral Akibat Aplikasi Material Kurang Tepat - Winny Yohana (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2013)
Oral health depends on the integrity of the mucosa. In the immune system, including skin, mucosa, respiratory tract is a leading of defense against infection. Microorganisms and dental materials in the oral cavity are foreign objects that can cause immune system reactions. The immune system coordinated by lymphocytes. The reaction of the immune system allows you to maintain the integrity of the body to an antigen, eliminating the aged cell (homeostasis), and to control death cell. The reaction of the immune system can occur naturally or specific. An important factor in the immunity of the oral cavity is a function of the integrity of the oral mucosa and salivary components. Secretory immunoglobulin A is the most important immunoglobulin in the saliva, and provide an important role to the protection of the oral mucosa from infection